2012
DOI: 10.1002/macp.201290042
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Chem. Phys. 14/2012

Abstract: Cover: 2D conjugated microporous polymers (CMPs) composed of alternate phenylene and ethynylene units are synthesized by cross‐coupling polymerization of 1,3,5‐triethynylbenzene and 1,3,5‐tribromobenzene. Spherical, tubular, and plate‐like structures are produced during the polymerization by varying the organic solvent used, and hence the organic solvent storage capacity can be altered. Further details can be found in the article by D. Tan, W. Fan, W. Xiong, H. Sun, Y. Cheng, X. Liu, C. Meng,* A. Li,* and W. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 0 publications
3
37
0
Order By: Relevance
“…The peak closes to 3050 cm −1 which is corresponded to the Ar‐H stretching vibration. While the third peaks is close to 2200 cm −1 corresponding to CC stretching vibration, although it can be clearly seen from the graph and its absorption peak is generally unconspicuous . The absorption bands at 2850–2960 cm −1 can be ascribed to the alkyl chain groups stretching vibration (C‐H).…”
Section: Resultsmentioning
confidence: 93%
“…The peak closes to 3050 cm −1 which is corresponded to the Ar‐H stretching vibration. While the third peaks is close to 2200 cm −1 corresponding to CC stretching vibration, although it can be clearly seen from the graph and its absorption peak is generally unconspicuous . The absorption bands at 2850–2960 cm −1 can be ascribed to the alkyl chain groups stretching vibration (C‐H).…”
Section: Resultsmentioning
confidence: 93%
“…The type of polymerization solvent, however, could affect the architecture of PDEBs by affecting the participation of reaction modes by which the pendant ethynyl groups of DEB monomeric units are transformed (intermolecular crosslinking, intramolecular cyclization). Also the conformational structure of PDEBs could be affected by the polymerization solvent via the solvent impact on the packing of PDEB segments. We speculate that the influence of the polymerization solvent on PDEB texture reflects the influence of the solvent on architecture and/or conformational structure of PDEBs.…”
Section: Resultsmentioning
confidence: 99%
“…The micromorphologies/shapes of CMPs play a critical role in their physical properties and ultimate applications, since the diffusion pathway of adsorbate molecules into porous networks depends on the outer shape of CMPs . Our previous work has confirmed the significant role of the morphologies of CMPs, which influence the physicochemical properties and the adsorption performance remarkably …”
Section: Introductionmentioning
confidence: 63%
“…In 2012, we observed the unexpected formation of microporous organic nanotubes, during the synthesis reaction of 1,3,5‐triethynylbenzene with 1,3,5‐tribromobenzene in p ‐xylene solvent. The scanning electron microscope (SEM) images in our study demonstrated that those CMP networks possessed a certain degree of hollow tubular structures in short range . Later by altering the building blocks through Hagihara‐Sonogashira coupling, we prepared other CMPs networks with tubular morphologies and hydrophobic sponges based on CMP tubes .…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation